Prognostic Factors for Liver Transplantation in Unresectable Hepatoblastoma - Triana Junco, Paloma; Cano, Esther María; Dore, Mariela; Jimenez Gomez, Javier; Sánchez Galán, Alba; Vilanova-Sánchez, Alejandra; Andres, Ane; Encinas, Jose Luis; Martinez, Leopoldo; Hernandez, Francisco; Lopez Santamaria, Manuel (European Journal of Pediatric Surgery, 2019)
Aim Hepatoblastoma is the most frequent hepatic tumor in children, and its initial presentation will affect treatment and prognosis. The aim of this study is to evaluate long-term results of liver transplantation in children with unresectable hepatoblastoma.Patients and Methods This is a retrospective review of patients with hepatoblastoma who underwent liver transplantation, analyzing risk factors, tumor presentation, treatment, and long-term survival to identify prognostic factors.Results Thirty-one patients underwent liver transplantation in the context of unresectable hepatoblastoma, mainly males (67%) and with risk factors such as prematurity (12.9%), maternal smoking (6.5%), and familial adenomatous polyposis (3.2%). Most frequent presentation was multifocal PRETEXT III (51.6%) and PRETEXT IV (45.2%), with metastasis at diagnosis in 12.9% and vascular involvement in 54.8%.Twenty-one patients received a living-donor (67.7%) and 10 a cadaveric graft (32.2%), at 31.7 months of age (5–125). Most transplants were primary, and only two were performed as rescue therapy after an attempt of surgical resection of the tumor.Overall survival 1 and 5 years after transplantation were 93.3% ± 4.6% and 86.4% ± 6.3%, respectively. We could not find any statistically significant differences between risk factors, tumor presentation, type of graft, or type of transplant.Conclusion Liver transplantation has increased hepatoblastoma survival in unresectable tumors. Probably due to these good results, we have not been able to find significant prognostic factors in this cohort.
Keywords: hepatoblastoma; liver transplantation; children; prognostic factors